Isolation and pharmacological characterization of α-Elapitoxin-Ot1a, a short-chain postsynaptic neurotoxin from the venom of the Western Desert Taipan, Oxyuranus temporalis - Barber, Carmel M.; Ahmad Rusmili, Muhamad Rusdi; Hodgson, Wayne C. (Multidisciplinary Digital Publishing Institute (MDPI), 2016)
Taipans (Oxyuranus spp.) are elapids with highly potent venoms containing presynaptic (β) and postsynaptic (α) neurotoxins. O. temporalis (Western Desert taipan), a newly discovered member of this genus, has been shown to possess venom which displays marked in vitro neurotoxicity. No components have been isolated from this venom. We describe the characterization of α-elapitoxin-Ot1a (α-EPTX-Ot1a; 6712 Da), a short-chain postsynaptic neurotoxin, which accounts for approximately 30% of O. temporalis venom. α-Elapitoxin-Ot1a (0.1–1 µM) produced concentration-dependent inhibition of indirect-twitches, and abolished contractile responses to exogenous acetylcholine and carbachol, in the chick biventer cervicis nerve-muscle preparation. The inhibition of indirect twitches by α-elapitoxin-Ot1a (1 µM) was not reversed by washing the tissue. Prior addition of taipan antivenom (10 U/mL) delayed the neurotoxic effects of α-elapitoxin-Ot1a (1 µM) and markedly attenuated the neurotoxic effects of α-elapitoxin-Ot1a (0.1 µM). α-Elapitoxin-Ot1a displayed pseudo-irreversible antagonism of concentration-response curves to carbachol with a pA2 value of 8.02 ± 0.05. De novo sequencing revealed the main sequence of the short-chain postsynaptic neurotoxin (i.e., α-elapitoxin-Ot1a) as well as three other isoforms found in O. temporalis venom. α-Elapitoxin-Ot1a shows high sequence similarity (i.e., >87%) with other taipan short-chain postsynaptic neurotoxins.